THE MIDDLE CAMBRIAN COSMOPOLITAN KEY SPECIES LEJOPYGE LAEVIGATA AND ITS BIOZONE: NEW DATA FROM SWEDEN - Axheimer N.; Eriksson M.E.; Ahlberg P.; Bengtsson A. (My University, 2006)
The middle Cambrian Lejopyge laevigata Zone is poorly exposed in Scandinavia. Both this zone, however, and the succeeding Agnostus pisiformis Zone are well exposed at a classic locality at Gudhem, Vastergotland, south-central Sweden. The sequences consist of finely laminated alum shale with scattered stinkstone (orsten) lenses. Three measured and sampled sections yielded a diverse fossil fauna, dominated by trilobites, in particular agnostoids, and the bradoriid Anabarochilina primordialis. Fossils are excellently preserved but restricted to the stinkstones. The L. laevigata Zone at Gudhem includes several geographically widespread key agnostoid species, notably Tomagnostella sulcifera, Clavagnostus spinosus, Glaberagnostus altaicus, Lejopyge laevigata and L. armata. The L. laevigata Zone in Scandinavia is here extended to include the traditional Solenopleura? brachymetopa Zone, and its lower boundary is defined by the FAD of L. laevigata. Trilobite evidence shows that the upper part of the Scandinavian L. laevigata Zone approximately correlates with the Proagnostus bulbus Zone of China and elsewhere.
Keywords: GLOBAL CORRELATION; BIOSTRATIGRAPHY; MIDDLE CAMBRIAN; LEJOPYGE LAEVIGATA ZONE; SWEDEN; Палеозой::Кембрийская; Paleozoic::Cambrian